Impact of Nonfullerene Acceptor Side Chain Variation on Transistor Mobility. (23rd July 2019) - Bristow, Helen; Thorley, Karl J.; White, Andrew J. P.; Wadsworth, Andrew; Babics, Maxime; Hamid, Zeinab; Zhang, Weimin; Paterson, Alexandra F.; Kosco, Jan; Panidi, Julianna; Anthopoulos, Thomas D.; McCulloch, Iain
Abstract: Organic photovoltaic power conversion efficiencies exceeding 14% can largely be attributed to the development of nonfullerene acceptors (NFAs). Many of these molecules are structural derivatives of IDTBR and ITIC, two common NFAs. By modifying the chemical structure of the acceptor, the optical absorption, energy levels, and bulk heterojunction morphology can be tuned. However, the effect of structural modifications on NFA charge transport properties has not yet been fully explored. In this work, the relationship between chemical structure, molecular packing, and charge transport, as measured in organic thin‐film transistors (OTFTs), is investigated for two high performance NFAs, namely O‐IDTBR and ITIC, along with their structural derivatives EH‐IDTBR and ITIC‐Th. O‐IDTBR exhibits a higher n‐type saturation field effect mobility of 0.12 cm 2 V −1 s −1 compared with the other acceptors investigated. This can be attributed to the linear side chains of O‐IDTBR which direct an interdigitated columnar packing motif. The study provides insight into the transport properties and molecular packing of NFAs, thereby contributing to understanding the relationship between chemical structure, material properties, and device performance for these materials. The high electron mobility achieved by O‐IDTBR also suggests its applications can be extended to use as an n‐type semiconductor in OTFTs. Abstract : The development of nonfullerene acceptors has been a key breakthrough in organic photovoltaics. However, the relationship between the chemical structures of these materials and their transport properties is not well understood. Here, organic thin‐film transistors are used to compare the mobilities of common nonfullerene acceptors.